Effectiveness of Ultrasound In Tennis Elbow Patients: Literature Review - Evandi Emohade, Erlansyah; Rahmadhanti, Khairisa; Nur Alpiah, Dini (International Journal of Social Research, 2024)
Lateral Epiconylitis Injury, also referred to as Tennis Elbow, is the result of tension of the common extensor tendon at the origin of the extensor carpi radialis brevis tendon. The method used is Literature Review. The results in this study were the effects of Ultrasound treatment on pain, hand grip strength, and functional elbow movement in patients diagnosed with Tennis Elbow. The conclusion of the study is that ultrasound intervention is effective in reducing pain and increasing grip strength in the hand, and also increasing functional elbow movement. The research results showed that Ultrasound modality therapy provided significant effectiveness p<0.01 in reducing pain.